Meningkatkan Motivasi Belajar Bahasa Inggris Middle Childhood di Panti Asuhan Sinar Damai Sejahtera Menjadi Lebih Baik - Bengkel Ginting; Novalin Hosio (Yayasan Literasi Sains Indonesia, 2022)
English As a foreign language, our ability to master English is very important in this four point zero era because English is not only used in education, but also in the world of work. However, we know that many Indonesians have low English skills, especially those from underprivileged groups such as orphans, abandoned children, children with disabilities (ADK). Many of the children at the Sinar Damai Sejahtera Orphanage are interested in learning English, but the unfavorable conditions for them, the very expensive English course, becomes an obstacle for them. Therefore, the Field Work Practice which has been carried out for 3 months is very useful for them to be able to learn English without having to pay any fees. The program intervention used in this PKL activity is the Community Intervention proposed by Zastrow which consists of: Intake, Assessment and Intervention Planning, Member Selection, Group Development, Evaluation and Termination. There has been an increase in reading and speaking skills in English with many positive impacts after this program.